1996
DOI: 10.1128/jvi.70.4.2208-2214.1996
|View full text |Cite
|
Sign up to set email alerts
|

Filovirus-induced endothelial leakage triggered by infected monocytes/macrophages

Abstract: The pathogenetic mechanisms underlying viral hemorrhagic fevers are not fully understood, but hemorrhage, activation of coagulation, and shock suggest vascular instability. Here, we demonstrate that Marburg virus (MBG), a filovirus causing a severe form of hemorrhagic fever in humans, replicates in human monocytes/macrophages, resulting in cytolytic infection and release of infectious virus particles. Replication also led to intracellular budding and accumulation of viral particles in vacuoles, thus providing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
120
1
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(123 citation statements)
references
References 42 publications
1
120
1
1
Order By: Relevance
“…Towards the terminal stage of infection and after the onset of hemorrhagic abnormalities, EBOV replicates in endothelial cells 27 . However, while endothelial cells are thought to play a role in pathogenesis, the molecular mechanisms that affect endothelial function are not yet fully understood 27,[71][72][73][74] .…”
Section: Filovirus Pathogenesismentioning
confidence: 99%
“…Towards the terminal stage of infection and after the onset of hemorrhagic abnormalities, EBOV replicates in endothelial cells 27 . However, while endothelial cells are thought to play a role in pathogenesis, the molecular mechanisms that affect endothelial function are not yet fully understood 27,[71][72][73][74] .…”
Section: Filovirus Pathogenesismentioning
confidence: 99%
“…Infection of monocytes and macrophages leads to the release of proinflammatory cytokines and chemokines, including tumor necrosis factor, interleukin-1β, macrophage inflammatory protein-1α and reactive oxygen and nitrogen species 11,12 . The expression of these mediators is likely to attract more monocytes and macrophages to the sites of infection and may also attract neutrophils.…”
Section: Host Immune Response To Fatal Ebola Infectionmentioning
confidence: 99%
“…The complete mechanisms leading to endothelium permeability have not been elucidated. Several studies have shown that the virally induced release of inflammatory mediators increases vascular permeability in vitro 11,51 . However, endothelial cells are targets of infection during later stages of the disease and direct virus-induced cytotoxicity of endothelial cells cannot be ruled out as a contributory mechanism for increased hemorrhagic manifestations.…”
Section: Vascular Impairment and Ebola Glycoproteinsmentioning
confidence: 99%
“…Though these C-type lectins show different specificities, depending on the structures of target glycans, all have been reported to promote filovirus entry. Hepatocytes, dendritic cells, monocytes and macrophages are thought to be the preferred target cells of filoviruses, and infection of these cells is important for hemorrhagic manifestation and immune disorders [20][21][22][23]. Thus, increased infection of these cells might be directly involved in the pathogenesis of filovirus infection [18,24].…”
Section: Introductionmentioning
confidence: 99%